Exceptionally heavy Rainfall in south Kerala on 17/8 October 1964 - DANIEL, E. J.; SUBRAMANIAM, A. H. (MAUSAM, 1966)
On 17/18 October 1964 exceptionally heavy rainfall occurred in the Trivandrum district of Kerala State. An attempt has been made to analyse the factors contributing towards this unusual phenomenon and its spatial distribution.